A new insight into the classification of Senna series Aphyllae (Leguminosae) - Robbiati, Federico Omar (2019)
A new classification in Senna Series Aphyllae based on distribution, morphology and phylogenetic evidences is proposed to contribute to a better comprehension of the series. Here, Senna aphylla var. divaricata and S. aphylla var. pendula are transferred to S. pachyrrhiza. Furthermore, S. rigidicaulis is considered a synonym of S. crassiramea, and a lectotype is designated for Cassia aphylla var. divaricata and C. crassiramea. Then, Series Aphyllae is composed by six species and two varieties.